TEACHING KNOWLEDGE AND THE TEACHING ACTION OF A RESIDENT TEACHER IN THE CONSTRUCTION OF TEACHING MATERIALS IN THE PEDAGOGICAL RESIDENCY PROGRAM (PERcursos Linguísticos, 2021)
The objective of this article is to present an analysis of the teaching activity, regarding the elaboration of didactic materials, developed by one of the academic participants of the Pedagogical Residency Program, Núcleo/Subprojeto de Letras-Português, carried out by the Federal University of XXXXXX. For this purpose, the article is based on the discussions held within the framework of Sociodiscursive Interactionism (BRONCKART, 2006, 2008), teaching knowledge (HOFSTETTER; SCHNEUWLY, 2009; VANHULLE, 2009), acting as a teacher, didactic repertoire (CICUREL, 2011) and modalizers of acting as a teacher (AUTORA, 2013). The methodology used, of a qualitative-interpretativist character (DENZIN; LINCOLN, 2005), started from the analysis of transcriptions of the presentation of a didactic material prepared and presented by the research collaborator. The analysis of the corpus shows some relevant aspects as to the mobilization of knowledge carried out by PR1 both for planning and for the possible use of the didactic material elaborated, which reveal representations of the actions of this teacher in initial formation regarding the teaching work, sometimes made possible by a set of knowledge that is legitimate to be teaching, sometimes limited by structural conditions that can interfere in the quality of the development of this work in the classroom.